NEUTRON DOSE ASSESSMENT USING SAMPLES OF HUMAN BLOOD AND HAIR. Issue 2 (7th November 2019) - Ekendahl, Daniela; Rubovič, Peter; Žlebčík, Pavel; Hupka, Ivan; Huml, Ondřej; Bečková, Věra; Malá, Helena
Abstract: The unique feature of nuclear accidents with neutron exposure is the induced radioactivity in body tissues. For dosimetry purposes, the most important stable isotopes occurring in human body, which can be activated by neutrons, are 23 Na and 32 S. The respective activation reactions are as follows: 23 Na(n, γ) 24 Na and 32 S(n, p) 32 P. While sodium occurs in human blood, sulfur is present in human hair. In order to verify the practical feasibility of this dosimetry technique in conditions of our laboratory, samples of human blood and hair were irradiated in a channel of a training reactor VR-1. 24 Na activity was measured by gamma-ray spectrometry. 32 P activity in hair was measured by means of a proportional counter. Based on neutron-spectrum calculation, relationships between neutron dose and induced activity were derived for both blood and hair.